2010
DOI: 10.2139/ssrn.1713987
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Labor Supply in Post-Conflict Tajikistan

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…Other studies that find negative labour participation effects for women include Acosta (2011), Cabejin (2006, Hanson (2007b), Lokshin and Glinskaya (2009), and Mendola and Carletto (2009). On the other hand, Justino and Shemyakina (2010) find the intriguing result that the negative effect of remittances on the labour supply is smaller for women than for men, a finding they explain in the context of Tajikistan's social conflict. Another interesting question is what migrant households do when they decrease their labour supply.…”
Section: Theoretical and Empirical Underpinningsmentioning
confidence: 94%
See 1 more Smart Citation
“…Other studies that find negative labour participation effects for women include Acosta (2011), Cabejin (2006, Hanson (2007b), Lokshin and Glinskaya (2009), and Mendola and Carletto (2009). On the other hand, Justino and Shemyakina (2010) find the intriguing result that the negative effect of remittances on the labour supply is smaller for women than for men, a finding they explain in the context of Tajikistan's social conflict. Another interesting question is what migrant households do when they decrease their labour supply.…”
Section: Theoretical and Empirical Underpinningsmentioning
confidence: 94%
“…Similarly, Görlich, Mahmoud, and Trebesch (2007); Gubert (2002), Jadotte (2009), and Justino and Shemyakina (2010) bring evidence of negative participation effects of remittances from Moldova, Mali, Haiti and post-conflict Tajikistan respectively. Some studies, however, find no significant impact of remittances on the labour supply (Funkhouser 2006;Yang 2008).…”
Section: Theoretical and Empirical Underpinningsmentioning
confidence: 97%
“…They provide essential economic and social support to reconstructing communities affected by violent conflict (Justino, ; Kumar, ; Moser and Clark, ; Rehn and Sirleaf, ). Several studies have reported an increase in female labour‐market participation in conflict‐affected countries, including in Afghanistan (Bove and Gavrilova, ), Indonesia (Adam, ), Timor‐Leste (Justino et al., ), Nepal (Menon and Rodgers, ), Tajikistan (Justino and Shemyakina, ) and Colombia (Calderón et al., ) — mostly in low‐skilled jobs in the informal sector (Justino et al., ; Kumar, ). Women also provide social services in areas affected by violent conflict, often voluntarily.…”
Section: Introductionmentioning
confidence: 99%
“…What they have in common instead is the experience of high inflows of capital, for Tajikistan mainly in the form of remittances (World Bank, 2006b) and for Romania largely from the EU (Duenwald, Gueorguiev, & Schaechter, 2007). At the same time, labor has migrated from both countries at high rates, resulting in a lower supply of labor (Justino & Shemyakina, 2012). Both flows make labor the relatively scarce production factor, thereby increasing the wage.…”
Section: Resultsmentioning
confidence: 99%